The Notary Role of Binding Guarantee on Land Rights in Credit Take Over Between Different Banks - Suyitno Suyitno; Nizar Anwar; Gunarto Gunarto (Jurnal Akta, 2019)
This study aims to: 1) to analyze the role of the notary on the binding guarantees the right to land in the credit of take over between different banks. 2) to analize the mechanismof binding process guarantees the right to land in the credit take over between different banks. The data used in this study are primary data, secondary data and data tertiary to support the process of this research, which was then analyzed by descriptive analysis method.Based on the results of data analysis can be concluded that: 1) relating the fine refinance loan, then the role of the Notary / PPAT should be promoting the principle of "Caution", because practice is very prone to take over the occurrence of consequences Particularly in binding legal guarantees and the imposition of Mortgage. 2). Take Over of credit can be done by way of subrogation, as well as a guarantee in the form of mortgage can be switched by-law without the need for plug. This is regulated in Article 16 Paragraph (1) of Act No. 4 of 1996 on Mortgage. But in practice, many banks are willing to take risks on lending without a guarantee that the imposition of Rights is not perfect dependents.Keywords: Role of the Notary; Binding Guarantee; Land rights; Credit Take Over